Mcluhan’s Theories and Convergence of Online and Papers' Newsrooms - Barceló-Sánchez, Juan Manuel; Gamonal Arroyo, Roberto; Barrientos-Báez, Almudena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The Internet convulsed journalism and created new press models based on budgets radically different from those that traditionally shaped the performance of the profession. Although at first the newspapers created different work structures for paper and web media, the final decision of the journalistic companies was to create a single newsroom for paper and web media. This article investigates if from the theory of Communication, and especially from the works of McLuhan, this decision is or is not justified in a correct way.